Adsorption kinetics of tea waste to catechins - Hu Shuqin; Tang Yi; Liu Li (浙江大学学报. 农业与生命科学版, 2014)
Catechins, the main functional components in tea, were generally recognized as possessing desirable biological and physiological effects, such as ant-i oxidation, ant-i cancer, reducing the risk of cardiovascular diseases etc. Therefore, application areas of tea catechins in food and pharmaceuticals were expanding rapidly. At present, conventional extraction technologies of catechins contained hot water extraction method, organic solvent extraction process, resin extraction method and supercritical CO2 extraction method. However, the application value was limited because of the low efficiency, high cost and potentially toxic residues. In order to extract catechins efficiently and safely, the recent studies found that lignocellulose could absorb catechins in abundance and in a low cost. Tea waste was used as a new kind of adsorbent in this paper. Because of the porous structure, it had large specific surface area. Meanwhile, the main components of tea waste were cellulose and protein. They all contained a mass of carboxyl groups and hydroxyl radicals which could form hydrogen bonds with catechins. The tea waste was similar to lignocellulose in structure and it was eatable, safe with no poisonous residue.The experiments were carried out as below. The equations of pseudo-first-order model and pseudo-second-order model were used to simulate the adsorption kinetics respectively. Then, different concentrations of ethanol were used to desorb the tea waste when it reached adsorption saturation. Finally, the same size tea waste was used to pack the chromatography column and the breakthrough curves of catechins and caffeine were drawn, then different concentrations of ethanol were used to elute the column gradely when it reached adsorption equilibrium. The results indicated that the kinetics were more fitted to the pseudo-second-order model (R2=0.913 6-0.997 1). The order of the secondary adsorption speed constant k2 was epigallocatechin gallate (EGCG)(0.000 5 g/(mg·min))< gallocatechin (GC)(0.000 9 g/(mg·min))< gallocatechin gallate (GCG)=epigallocatechin (EGC)(0.001 4 g/(mg·min))>epicatechin gallate (ECG)(0.001 5 g/(mg·min))>caffeine (0.002 3 g/(mg· min))>catechin (0.003 2 g/(mg·min))>epicatechin (EC)(0.011 8 g/(mg·min)). The initial adsorption rates h2 of the total catechins, ester catechins, EGCG, and caffeine were 7.622 0 mg/(g·min), 6.964 8 mg/(g·min), 4.178 2 mg/(g·min), 0.658 4 mg/(g·min) respectively. After adsorption, the ratio of caffeine to total catechins was changed from 0.164 to 0.079. The desorption experiments demonstrated that 40% alcohol could desorb the ester catechins sufficiently. As the desorption time prolonged, the desorption quantity of each component increased; the desorption quantity increased slowly from the 10th to 20th min, while it increased rapidly from the 20th to 30th min. After being desorbed for 30 min, the concentrations of EGCG, ester catechins, total catechins, caffeine were 1.996 mg/mL, 3.587 mg/mL, 3.982 mg/mL, 0.333 mg/mL respectively. The breakthrough curves on the packed column with tea waste showed that the caffeine was the earliest to be saturated, while ester catechins needed most time. And gradient ethanol desorption experiments showed that 10% ethanol could desorb most of caffeine but not catechins, while 40% ethanol could desorb most of the catechins. So it was possible that using the 10% ethanol to desorb caffeine firstly, then using 40% ethanol to desorb ester catechins to get high purity catechin products.It comes to a conclusion that tea waste can absorb catechins sufficiently and has a remarkable function on decaffeinating. Because of its characteristics of eatable, low-price, reproducible and non-pollution, it can be used as a new adsorbent. On the other hand, it can also provide a new reference on the recycling of tea waste.